Participatory culture across digital spaces between ethics and practical transgressions - A field study of a sample of students from Setif 2 University and Kasdi Merbah Ouargla University - Sousane SEKKI; Chafika MEHRI (Social Sciences Journal, 1970)
The study investigates the topic of participatory culture among university students within digital spaces, focusing on the interplay between ethical commitment and observed transgressions in practice. This inquiry is based on a field study involving students from Setif 2 University and Kasdi Merbah Ouargla University, aiming to delineate the characteristics and dimensions of this culture while monitoring any moral infractions. The ultimate goal is to enhance awareness among the target demographic regarding the potential risks associated with digital spaces, particularly those pertaining to ethical considerations.The results from the field research indicate a positive participatory culture among university students, characterized by its diverse components and dimensions. However, this culture is impeded by moral risks and violations that restrict positive interactions and the constructive exchange of ideas, experiences, and cultural perspectives.